GPS, GLONASS, Galileo, and BeiDou for Mobile Devices : From Instant to Precise Positioning - Petrovski, Ivan G. (Cambridge : Cambridge University Press, 2014)
Get up to speed on all existing GNSS with this practical guide. Covering everything from GPS, GLONASS, Galileo, and BeiDou orbits and signals to multi-GNSS receiver design, AGPS, RTK, and VRS, you will understand the complete global range of mobile positioning systems. Step-by-step algorithms and practical methods provide the tools you need to develop current mobile systems, whilst coverage of cutting edge techniques, such as the instant positioning method, gives you a head-start in unlocking the potential of future mobile positioning. Whether you are an engineer or business manager working in the mobile device industry, a student or researcher, this is your ideal guide to GNSS.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).
Keywords: Mobile communication systems; Global positioning system; Galileo satellite navigation system; Artificial satellites in navigation